External injuries in green turtles (Chelonia mydas) submitted to necropsia in the external injuries in green turtles (Chelonia mydas) submitted to necropsia in the tamar project of Ubatuba in the period from november 2015 to june 2016amar project of Ubatuba in the period from november 2015 to june 2016 - Arduini, I. T.; Tasaka, A. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Chelonia mydas, also known as the Green Turtle, or Aruanã, is present in tropical and subtropical areas of the world and performs complex migratory strategies, and has been reported on the coast of at least 140 countries (LAGUEUX, 2001). The region of Ubatuba is a feeding place for several juvenile turtles and it is not uncommon to find it adrift, or on the beach. Chelonia mydas is included in the Red List of species threatened by International Union for Conservation of Nature (IUCN). The Ubatuba Tamar Project carries out an important environmental protection action, through environmental education and treatment of sick or non-returnable animals. External injuries in marine animals may be due to normal predation in nature, but may also result from human action. When sea turtles die in good nutritional state, the suspicion is of severe injury, resulting from contact with boats, or by fishing nets and lines, with consequent drowning (SALES et al., 2003). Objective: The aim of this study was to analyze the external lesions commonly found in animals taken at necropsy in the Ubatuba Tamar Project (Latitude: -23.45229; Longitude: -45.07126), São Paulo-Brazil, during the period from November 2015 to June 2016.